2003
DOI: 10.1023/a:1021786811186
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order for empirically validated school-based prevention programs to "go to scale," it is important to understand the processes underlying program dissemination. Data collected in effectiveness trials, especially those measuring the quality of program implementation and administrative support, are valuable in explicating important factors influencing implementation. This study describes findings regarding quality of implementation in a recent effectiveness trial conducted in a high-risk, American urban commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
110
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(125 citation statements)
references
References 32 publications
7
110
0
8
Order By: Relevance
“…Finally, schools that engaged in local program selection and training, integrated the chosen programs into normal school operations, and chose standardized programs were likely to have more frequent student participation in both individual-and environmentallevel programs. These findings are also consistent with other prior literature that has found that principal support, program standardization, high quality training, and integration into normal school operations are all related to high quality program implementation (Bosworth et al 1999;Elliot and Mihalic 2004;Ennett et al 2003 and Mihalic 2003;Fullan 1991;Gingiss et al 2006;Jaycox et al 2006;Kam et al 2003;Louis and Miles 1990;McCormick et al 1995;Mihalic et al 2008;Olds 2002;Schoenwald and Hoagwood 2001;Roberts-Gray et al 2007;Rohrbach et al 1993Rohrbach et al , 2006Weissberg and O'Brien 2004). In addition, several relationships between the exogenous characteristics and characteristics of the schools and programs were also found in both models; these findings are also consistent with prior studies Payne et al 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, schools that engaged in local program selection and training, integrated the chosen programs into normal school operations, and chose standardized programs were likely to have more frequent student participation in both individual-and environmentallevel programs. These findings are also consistent with other prior literature that has found that principal support, program standardization, high quality training, and integration into normal school operations are all related to high quality program implementation (Bosworth et al 1999;Elliot and Mihalic 2004;Ennett et al 2003 and Mihalic 2003;Fullan 1991;Gingiss et al 2006;Jaycox et al 2006;Kam et al 2003;Louis and Miles 1990;McCormick et al 1995;Mihalic et al 2008;Olds 2002;Schoenwald and Hoagwood 2001;Roberts-Gray et al 2007;Rohrbach et al 1993Rohrbach et al , 2006Weissberg and O'Brien 2004). In addition, several relationships between the exogenous characteristics and characteristics of the schools and programs were also found in both models; these findings are also consistent with prior studies Payne et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Schools with greater organizational capacity, indicated by characteristics such as amenability and communication, display greater implementation quality (Bosworth et al 1999;Elliot and Mihalic 2004;Ennett et al 2003;Fullan 1992; Jaycox et al 2006;Louis and Miles 1990;McLaughlin 1990;Olds 2002;Payne et al 2006;Mihalic et al 2008;Rohrbach et al 2006;Schoenwald and Hoagwood 2001;Sobeck et al 2006;Stoll and Fink 1996). Similarly, schools with greater organizational support, such as program provider training and principal support are better equipped to implement prevention programs (Bosworth et al 1999;Desimone et al 2004;Elliot and Mihalic 2004;Ennett et al 2003;Fagan and Mihalic 2003;Fullan 1991;Gingiss et al 2006;Jaycox et al 2006;Kam et al 2003;Louis and Miles 1990;McCormick et al 1995;Olds 2002;Payne et al 2006;Roberts-Gray et al 2007;Schoenwald and Hoagwood 2001;Rohrbach et al 1993Rohrbach et al , 2006Weissberg and O'Brien 2004). Related to this, schools that do a better job of integrating the program into normal school operations and local initiation and planning display higher program implementation quality (Bosworth et al 1999;Jaycox et al 2006;Mihalic et al 2008;…”
mentioning
confidence: 99%
“…These, in turn, should lead to improved student outcomes. However, while a teacher may implement a program with high fidelity, in the absence of a supportive school setting positive program outcomes are not always guaranteed (Kam et al 2003;Sheldon 2005).…”
mentioning
confidence: 99%
“…Of these characteristics, several of the more robust associations with high fidelity of implementation are a supportive administration (Connell et al 1985;Elliott and Mihalic 2004;Kam et al 2003;Payne et al 2006;Rohrbach et al 1993;Smith et al 1993) and support for a program received from one's peer group (i.e., teachers) and other school personnel (McCormick et al 1995;Sheldon 2005). These components of a school's climate are, in turn, posited to influence those who come into continuous contact with it (Gittelsohn et al 2003;Rogers 1995Rogers , 2002.…”
mentioning
confidence: 99%
“…Findings from efficacy studies lend indirect support to this perspective, because implementing classroom management strategies is necessary, but not sufficient for obtaining significant intervention effects. For example, Paths to Alternative Thinking Strategies (PATHS) Curriculum included consultations in the teacher training, which were found to foster positive effects and facilitate high quality implementation of activities designed to develop children's social and emotional competencies (Kam, Greenberg, and Walls 2003;Domitrovich, Cortes, and Greenberg 2007). Consequently, our teacher training component was aimed at acquiring classroom management skills and coaching skills for supporting children in acquiring age-appropriate social and emotional competencies.…”
mentioning
confidence: 99%